Distributed Temperature Sensing and Real Time Thermal Rating for Underground Power Cable Monitoring - Wiroj Tangtheerajaroonwong; Phiphat Tanapornchinpong; Boonsak Kiatjaroonlert; W. Khan-ngern; Chanintorn Sangracha; Chaiyan Jettanasen (My University, 2025)
This paper presents the distributed temperature sensing (DTS) technology and its application mainly on underground power cables. The main measuring principle is detecting the back-scattering light via Raman scattering that varies and depends on temperature at each point of optical fiber. In this paper, the authors present the monitoring results that the load current is applied for 50% of the rated current of the 69 kV and 115 kV transmission cables, and the DTS detects temperature increasing 0.5°C from the ambient temperature. This paper also shows real time thermal rating for calculations of conductor temperature.
Keywords: Thermal Analysis in Power Transmission; High voltage insulation and dielectric phenomena; Electrical Fault Detection and Protection